2011
DOI: 10.3168/jds.2011-4318
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir and routes of transmission of Enterobacter sakazakii (Cronobacter spp.) in a milk powder-producing plant

Abstract: Several outbreaks of Cronobacter spp. (Enterobacter sakazakii) have been described as food-borne illness in neonates and infants. Powdered infant formula has been identified as a source of infection, especially in hospital nurseries, where a bulk of formula nutrient is prepared for the whole day and instructions for preparation are not always followed correctly. Neonates who are underweight or immunosuppressed are especially at risk for an E. sakazakii infection. Considering that milk powder is the main ingred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 31 publications
(35 reference statements)
2
36
0
Order By: Relevance
“…ST1 is a dominant ST consisting of strains isolated from across the world over a period of more than 25 years. These have been mainly isolated from PIF and clinical cases, and also more recently from milk powder processing factories in Germany and Australia (Craven et al, 2010; Jacobs et al, 2011), apart from a few food isolates. ST14, which is a SLV ( ppsA allele) of ST1 was isolated from infant formula (Caubilla-Barron et al, 2007).…”
Section: Clonalitymentioning
confidence: 99%
“…ST1 is a dominant ST consisting of strains isolated from across the world over a period of more than 25 years. These have been mainly isolated from PIF and clinical cases, and also more recently from milk powder processing factories in Germany and Australia (Craven et al, 2010; Jacobs et al, 2011), apart from a few food isolates. ST14, which is a SLV ( ppsA allele) of ST1 was isolated from infant formula (Caubilla-Barron et al, 2007).…”
Section: Clonalitymentioning
confidence: 99%
“…Twelve strains of C. sakazakii that were isolated from PIF collected in 12 countries were shown to be ST4. Fifteen strains which had been isolated from milk-processing factories, including roller dryers, tanker bays, and spray dryers, in Australia and Germany (6,21) were revealed to be ST4. Other nonclinical sources included isolates from weaning food, chocolate (44), and a washing brush (46).…”
Section: Mlst Of the Genusmentioning
confidence: 99%
“…Some contamination of the fi nished product was traced to the dry blending of ingredients. A number of studies have shown that the supply air is a potential vehicle for Cronobacter contamination and confi rmed that the organism is dispersed widely in milk powder factories Hein et al 2009 ;Craven et al 2010 ;Reich et al 2010 ;Jacobs et al 2011 ). These early studies on strain persistence should be considered along with more recent observations of C. sakazakii ST4 presence in manufacturing plants and fi nished products.…”
Section: Pathogenicity Of Cronobacter Spp and Infant Infectionsmentioning
confidence: 99%
“…These were divided into 13 pulsetypes. Although the original studies by Craven et al ( 2010 ) and Jacobs et al ( 2011 ) did not speciate the Cronobacter strains, these have now been reanalysed using MLST (Sonbol et al 2013 ). It revealed that C. sakazakii was the predominant Cronobacter species isolated from the 6 factories and that nearly a third of the strains (21/72) were C. sakazakii clonal complex ST4, the lineage associated with neonatal meningitis.…”
Section: Pathogenicity Of Cronobacter Spp and Infant Infectionsmentioning
confidence: 99%
See 1 more Smart Citation